Characterization of CPH:SA microparticle‐based delivery of interleukin‐1 alpha for cancer immunotherapy - M. M. Hasibuzzaman; Rui He; Ishrat Nourin Khan; Rasna Sabharwal; Aliasger K. Salem; Andrean Llewela Simons‐Burnett (Wiley, 2023)
Abstract Background Interleukin‐1 alpha (IL‐1α) is a pro‐inflammatory cytokine that can activate immune effector cells and trigger anti‐tumor immune responses. However, dose‐limiting toxicities including cytokine storm and hypotension has limited its use in the clinic as a cancer therapy. We propose that polymeric microparticle (MP)‐based delivery of IL‐1α will suppress the acute pro‐inflammatory side effects by allowing for slow and controlled release of IL‐1α systemically, while simultaneously triggering an anti‐tumor immune response. Methods Polyanhydride copolymers composed of 1,6‐bis‐(p‐carboxyphenoxy)‐hexane:sebacic 20:80 (CPH:SA 20:80) was utilized to fabricate MPs. Recombinant IL‐1α (rIL‐1α) was encapsulated into CPH:SA 20:80 MPs (IL‐1α‐MPs) and the MPs were characterized by size, charge, loading efficiency, and in‐vitro release and activity of IL‐1α. IL‐1α‐MPs were injected intraperitonially into head and neck squamous cell carcinoma (HNSCC)‐bearing C57Bl/6 mice and monitored for changes in weight, tumor growth, circulating cytokines/chemokines, hepatic and kidney enzymes, blood pressure, heart rate, and tumor‐infiltrating immune cells. Results CPH:SA IL‐1α‐MPs demonstrated sustained release kinetics of IL‐1α (100% protein released over 8-10 days) accompanied by minimal weight loss and systemic inflammation compared to rIL‐1α‐treated mice. Blood pressure measured by radiotelemetry in conscious mice demonstrates that rIL‐1α‐induced hypotension was prevented in IL‐1α‐MP‐treated mice. Liver and kidney enzymes were within normal range for all control and cytokine‐treated mice. Both rIL‐1α and IL‐1α‐MP‐treated mice showed similar delays in tumor growth and similar increases in tumor‐infiltrating CD3+ T cells, macrophages, and dendritic cells. Conclusions CPH:SA‐based IL‐1α‐MPs generated a slow and sustained systemic release of IL‐1α resulting in reduced weight loss, systemic inflammation, and hypotension accompanied by an adequate anti‐tumor immune response in HNSCC‐tumor bearing mice. Therefore, MPs based on CPH:SA formulations may be promising as delivery vehicles for IL‐1α to achieve safe, effective, and durable antitumor responses for HNSCC patients.